Education under the shadow in Southern European countries. Implications for equity - Ariadne Runte-Geidel (Universidad Nacional de Educación a Distancia (UNED), 2015)
Nowadays most educational research focuses on formal education. However it is gradually recognizing the existence of a parallel education system that accompanies the formal system as if was its own shadow. The shadow education is a system based on the laws of the market, still poorly regulated and under-researched. This comparative study aims to determine the prevalence of shadow education in Spain and countries in its geographical and cultural context, also examine their implications in the different countries studied. Analyzes carried out show high rates of use of shadow education in all countries studied and similarities in the effects on social equity. The findings point to the need for regulation of the sector and infer about problems in formal systems as the possible cause of the high rates of shadow education are found.